THE IMPACT OF ISLAMIC RELIGIOSITY ON INNOVATIVE WORK BEHAVIOR WITH MEDIATING ROLE OF KNOWLEDGE SHARING AND ORGANIZATIONAL POLITICS AS MODERATOR - Mazhar Farooq Atif; Mobashira Alvi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This study examines the relationship between Islamic religiosity and innovative working behavior with the mediating role of knowledge sharing and moderator as an Organizational politics from a Self-Determination Theory perspective. The specific context of the study is the TEVTA education sector, particularly in South Punjab, Pakistan. It is assumed that Islamic religiosity, innovative working behavior, knowledge sharing, and Organizational politics are the sources of improvement and improved performance of the TEVTA education sector in Pakistan. Data were collected using a questionnaire of 270 employees working at the TEVTA Institute in southern Punjab. Results indicate that Islamic religiosity has a positive and significant impact on innovative work behavior. Moreover, the mediating role of knowledge sharing has also an established and positive relationship between Islamic religiosity and innovative working behaviour. The results also confirm the moderating role of Organizational politics. In the end, the study sets out the implications for both (academic and managerial) and suggests options for recommendations, study limitations, and a basis for future directions for further research.